Changes in white matter predict efficacy of repetitive transcranial magnetic stimulation in Parkinson's disease - Jinying Han; Lingling Lv; Xin Chen; Mengqi Wang; Lili Hu; Fengbo Xing; Pingping Liu; Liuzhenxiong Yu; Ziye Zhao; Jinmei Sun; Tingting Liu; Jingjing Cheng; et al. (NeuroImage)
Background: The efficacy of continuous theta burst stimulation (cTBS) in Parkinson's disease (PD) exhibits considerable variability. Emerging evidence links changes in brain white matter (WM) activity to the onset and progression of PD, offering novel insights into its pathophysiology. Objective: Exploring activity patterns within different WM regions to predict the therapeutic efficacy of cTBS. Methods: This retrospective study included 68 patients with PD who underwent a 14-day cTBS targeting the supplementary motor area (25,200 pulses). Patients were classified as responders (R, n = 20) or non-responders (NR, n = 48) based on whether their UPDRS III score improved by ≥30 %. Pre-intervention differences in WM amplitude of low-frequency fluctuations (ALFF) and fractional ALFF in fMRI were analyzed, along with their correlation with motor symptom improvement. A support vector machine (SVM) model was developed to predict cTBS efficacy and validated in an independent cohort (n = 22). Results: Compared to the NR group, R patients exhibited greater improvements in rigidity and axial symptoms, accompanied by lower baseline ALFF in multiple WM tracts. SVM analysis identified higher baseline UPDRS III and rigidity scores, along with reduced ALFF in the left corticospinal tract, right ILF, and left anterior thalamic radiation, as predictors of better motor outcomes. In an independent cohort, predicted and actual UPDRS III improvements showed a concordance correlation coefficient (CCC) of 0.630. A combined model incorporating rigidity scores and ILF_R ALFF achieved moderate accuracy in predicting rigidity improvement (CCC = 0.725). Conclusion: Baseline WM function may serve as a biomarker for predicting motor response to cTBS.